The Current Dilemma and Breakthrough of Stem Cell Therapy in Ischemic Heart Disease - Liu, Chuanbin; Han, Dong; Liang, Ping; Li, Yang; Cao, Feng (Frontiers in Cell and Developmental Biology, 2021)
Ischemic heart disease is the leading cause of mortality worldwide. Stem cell transplantation has become a promising approach for the treatment of ischemic heart disease in recent decades. It is generally recognized that preclinical cell-based therapy is effective and have yielded encouraging results, which involves preventing or reducing myocardial cell death, inhibiting scar formation, promoting angiogenesis, and improving cardiac function. However, clinical studies have not yet achieved a desired outcome, even multiple clinical studies showing paradoxical results. Besides, many fundamental puzzles remain to be resolved, for example, what is the optimal delivery timing and approach? Additionally, limited cell engraftment and survival, challenging cell fate monitoring, and not fully understood functional mechanisms are defined hurdles to clinical translation. Here we review some of the current dilemmas in stem cell-based therapy for ischemic heart disease, along with our efforts and opinions on these key issues.